الاجتهاد بتحقيق المناط وأثره في الاختلاف في النوازل الطبية المعاصرة - كتال رضوان (Universty Of El-oued جامعة الوادي, 2024)
الملخص: هذا البحث عبارة عن دراسة لأهم أركان عملية الاجتهاد، وهو الذي يعول عليه لتطبيق أحكام الشريعة الإسلامية على أرض الواقع، ولطالما اهتم الأصوليون بضبط مباحث الاجتهاد، لكنهم اختلفوا في حقيقة الاجتهاد بتحقيق المناط، أهو مندرج ضمن مباحث العلة أم أنه مندرج ضمن أبواب الاجتهاد؟ وهذا الخلاف الأصولي أدى إلى خلاف في الفروع الفقهية خاصة فيما يستجد للناس من حوادث ونوازل في مختلف المجالات، وخاصة في المجال الطبي، لما حصل من تطور فيه من ناحية الدراسات والأبحاث ومن ناحية الأجهزة والمعدات، لذلك جاءت هذه الدراسة للنظر في ماهية الاجتهاد بتحقيق المناط وضبط معالمه وتتبع آثاره في الخلاف في النوازل الطبية المعاصرة. ومن أجل الإجابة على هذا الإشكال، والوصول إلى المبتغى من وراءه، جاء هذا البحث في مقدمة وبابين وخاتمة، اعتنى الباب الأول منها بالاجتهاد بتحقيق المناط، واشتمل على فصلين الفصل الأول خصصته لماهية الاجتهاد بتحقيق المناط، والثاني كان لبيان علاقة الاجتهاد بتحقيق المناط بمقاصد الشريعة، أما الباب الثاني فكان في النوازل الطبية المعاصرة، واشتمل أيضا على فصلين الفصل الأول بينت فيه معالم الاجتهاد في النوازل الطبية المعاصرة، والفصل الثاني كان لنماذج تطبيقية في النوازل الطبية المعاصرة. وتوجت الدراسة بخاتمة حوت أهم النتائج المتوصل إليها، والتي من أهمها أن الاجتهاد بتحقيق المناط ضرب من أضرب الاجتهاد، ولا يمكن أن يستغني عنه مجتهد ولا مفت ولا قاض حتى المكلف العامي، فهو السبيل لتفعيل أحكام الشريعة الإسلامية وإنزالها من إطارها النظري المجرد إلى العملي الواقعي، وتبين من خلال النماذج في النوازل الطبية أن الاختلاف في تحقيق المناط سبب من أسباب الاختلاف في الأحكام الفقهية للنوازل الطبية المعاصرة. Résumé : فرنسية أو انجلزية This research is a study of the most important pillars of the process of ijtihad and it is he who relied upon to apply the provisions of Islamic law on the ground. Fundamentalists have always been interested in controlling the investigations of ijtihad but they differed in the truth of ijtihad in the investigation of the areas. This fundamentalist disagreement has led to a disagreement in the jurisprudential branches especially with regard to new accidents and catastrophes for people in various fields especially in the conflict in contemporary medical calamities. In order to answer this problem and reach the target behind it this research came in an introduction two sections and a conclusion the first chapter of which was concerned with ijtihad to achieve the objective and it included two chapter the first chapter devoted it to the essence of ijtihad to explain the relationship of ijtihad to the achievement of the mandates with the objectives of sharia as for the second chapter it was about contemporary medical issues and it also included two chapters the first chapter showed the features of ijtihad in contemporary medical issues and the second chapter was for applied models in contemporary medical issues. The study culminated in the conclusion of the most important conclusions reached the most important of which are that the ijtihad to achieve the assignment is a form of the most striking of ijtihad and a mujtahid mufti or judge cannot be dispensed with even the public commissioner as it is the way to activate the provisions of Islamic law and bring it down from its abstract theoretical framework to realistic in the medical calamities.
أطروحة دكتوراه تخصص الفقه و أصوله في العلوم الإسلامية
Keywords: لنوازل الطبية – الإجتهاد – الإختلاف - بتحقيق المناط; Medical calamities - diligence - disagreement - achieving the goal